Fundamental Challenges and Management Opportunities in Post Disaster Reconstruction Project - Meervat R. Altaie; Marwa Makki Dishar; Ibrahim F. Muhsin (Salehan Institute of Higher Education, 2023)
The study examines the root causes of delays that the project manager is unable to resolve or how the decision-maker can identify the best opportunities to get over these obstacles by considering the project constraints defined as the project triangle (cost, time, and quality) in post-disaster reconstruction projects to review the real challenges to overcome these obstacles. The methodology relied on the exploratory description and qualitative data examined. 43 valid questionnaires were distributed to qualified experienced engineers. A list of 49 factors causes was collected from previous international and local studies. A Relative Important Index (RII) is adapted to determine the level of importance of each sub-criterion in the four main criteria (scope, time, cost, and quality) to represent the causing changes in projects. The concluded 13 important factors represent the challenges faced by managers. This process requires active participation in the management role to overcome potential delays that face a great challenge and cause huge waves of displacement that affect the Iraqi economy and lead to social and environmental modifications. Reconstruction projects create jobs, improve the quality of life, and encourage people to return to their homes and rebuild their cities. So, unlocking local potential is the key to sustainable rebuilding in Iraq.Â Doi: 10.28991/CEJ-2023-09-09-05 Full Text: PDF